ERECTA-Family Receptor Kinases Regulate Stem Cell Homeostasis via Buffering its Cytokinin Responsiveness in the Shoot Apical Meristem - Uchida, Naoyuki (Oxford University Press, 2013)
Shoot apical meristems (SAMs), which are maintained at the tips of stems, are indeterminate structures and sources of stem cells from which all aerial organs are ultimately derived. Although mechanisms that regulate the homeostasis of the stem cells have been extensively investigated, identification of further unknown regulators should provide better understanding of the regulation. Here, we report that members of the Arabidopsis ERECTA (ER) receptor kinase family redundantly play a significant role in the regulation of stem cell homeostasis. In wild-type seedlings, the expression of WUSCHEL (WUS), a central regulator of the stem cell population, is stimulated by cytokinin. Interestingly, however, the SAM morphology and the expression of CLAVATA3 (CLV3), which is expressed in stem cells and therefore serves as a stem cell marker, are relatively stable against cytokinin treatment regardless of increased WUS expression. These findings indicate the presence of a mechanism to buffer stem cell homeostasis against an increase in cytokinin. Mutant seedlings lacking all ER-family members, which are expressed in the SAM, show an increase in the stem cell population and also the up-regulation of a cytokinin-responsive gene in the SAM. In this mutant, WUS expression is stimulated by cytokinin treatment as efficiently as in wild-type plants. However, in contrast to wild-type plants, SAM morphology and CLV3 expression respond drastically to cytokinin treatment, suggesting that the buffering mechanism to maintain stem cell homeostasis against an increase in cytokinin is severely impaired in this mutant. We suggest that the ER family regulates stem cell homeostasis via buffering its cytokinin responsiveness in the SAM.